Konsep Self-Interest dan Maslahah dalam Rasionalitas Ekonomi Islam - Dede Nurohman (Islamica: Jurnal Studi Keislaman, 2010)
Two important concepts in economics represent the main ideas that this paper is concerned with, namely the concept of self-interest and mas lah ah. These two concepts will be analyzed in the light of what is commonly known as the economic rationality. The rational dimension of economy is about the individual act in consumption and production. An act in consumption and production?like in any other acts?is called rational as long as it is line with one?s logic. When an act is done not in a proper concordance with logic, then the act is not rational. Pure Capitalism in which one would justify his/her acts of oppressing others economi cally for example, cannot be called rational because it is not logical and is not in a proper consonance with the ethical values. We argue therefore that the rational dimension coupled with its ethical apparatus must represent the heart of all economic activities if a healthy economic foundation is to be established. Here we contend that self-interest?as opposed to maslahah?hasno place whatsoever in the whole schemata of rational economy. On the contrary, mas lahah is an alternative for the already hegemonic system of global economy in which self-interest is its core. Maslahah ah is to do with society-interest and not self-interest. At the end, this paper is a critique against the global capitalistic economy that has failed to establish justice and equality for all.